Further evidence of altered redox status of hyperbilirubinaemic patients: role of bilirubin in Gilbert syndrome - Hagymási, Krisztina (Acta Biologica Szegediensis, 2003)
Bilirubin is regarded as the most powerful endogenous antioxidant substance. It exhibits immunmodulator, inhibitor activities on kinases, yet it is clear that it can be potentially cytotoxic. Gilbert syndrome is characterised by hereditary, chronic, mild unconjugat-ed hyperbilirubinaemia. 12 Gilbert syndrome patients and 15 healthy controls were investigat-ed with special regard to reduction-oxidation status and free radical-antioxidant balance. Sera free SH-group concentration, H-donating ability, reducing power were measured spec-trophotometric methods. Total scavenger capacity, describing free radical-antioxidant balance, was determined by a newly developed chemiluminometric method in sera, plasma and erythrocytes. Patients with Gilbert syndrome showed a significant increase of non-enzymatic antioxidant capacity. Elevated free SH-group concentration, H-donating ability and reducing power were found in mild hyperbilirubinaemia compared with control group patients. On the other hand no significant differences were detected regarding free radical-antioxidant balance in sera, plasma and erythrocytes between the groups. On the basis of these results it can be supposed that elevated bilirubin concentration, via indirect or compensatory way, strengthens non-enzymatic antioxidant capacity, without changes in antioxidant-free radical balance. That is why further investigations are needed to clarify the consequences of elevated bilirubin concentration on cell redox homeostasis.